PENGARUH MOTIVASI KERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK YANG ADA DI BPJS KETENAGAKERJAAN KOTA MANADO - LENGKONG, LAURITA; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: the incidence of complaints from the public against BPJS employment in Manado city due to insufficient services areprovided. Based on this research background the purpose of this research was to describe the influence of motivation ofworking employees to quality public services that exist in the BPJS Manado city Employment.In this study the methods used i.e. quantitative methods, using the approach to the analysis of correlationand simple linear regression analysis. Because of the use of quantitative research, then the researchers in this study intends toanalyze the extent of variations or other factors more based on coefficients of korelasinyaThe results showed Labor Motivation in Employment BPJS Manado is generally not well seen from the indicator measurementsused i.e., passionate and spirited, satisfaction in work, creativity and participation, responsibility, work productivity. The qualityof public services in the Employment Office of the BPJS Manado city seen from the indicator used Reliability, Assurances,Tangible, Responsiveness, Empath was enough of a maximumKeywords: motivation, quality of service